Unveiling the Mediating Role of Omnichannel Behavior Agility between Service Agility and Marketing Performance: Mengungkap Peran Mediasi Kelincahan Perilaku Omnichannel antara Kelincahan Layanan dan Kinerja Pemasaran - Dimas Wibisono; Dwi Taufik Rohman; Rasyiid Yoga Pradita; Tsania Ayu Rohani (Universitas Muhammadiyah Sidoarjo, 2026)
This study investigates how service agility influences marketing performance among micro, small, and medium enterprises (MSMEs) in Sleman, Yogyakarta, with a focus on the mediating role of omnichannel behaviour agility. Grounded in Service–Dominant Logic (SDL), the research conceptualizes service agility as the ability to deliver services quickly and flexibly, while omnichannel behaviour agility refers to consumers’ seamless adaptation across digital and physical channels. A quantitative approach was employed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) via SmartPLS 3.0, analyzing data from 135 MSME owners collected between March and May 2025. Results show that service agility has a significant positive impact on marketing performance both directly and indirectly through enhanced omnichannel behaviour agility. The findings underscore the importance of aligning organizational responsiveness with consumer channel adaptability to drive sales growth, market share, customer satisfaction, and retention. This study extends SDL theory by emphasizing co-created value in omnichannel environments and offers practical guidance for MSMEs aiming to strengthen competitiveness in rapidly digitalizing markets.